Improvement of the Mechanical Properties of Plant Fiber-reinforced Composites through Hybridization - GENÇ, GARİP (TAYLOR & FRANCIS INC, 2022)
The most important reason why natural fibers are not sufficiently involved in applications is the large scattering of their properties. In addition, it is very difficult to find one kind of natural fiber which has perfect mechanical properties like synthetic fibers. Here, we aimed to find solutions by developing a hybrid composite according to the expectations in the field of application. With this method, desired mechanical properties can be designed, and the weak properties can be improved. To be able to examine this method, we used two different fibers which have different mechanical characteristics. The mechanical properties were measured with three-point bending and impact resistance tests. According to the results, the flexural strength of the jute-reinforced composites (JC) has been improved by 44-71% using luffa fiber hybridization method. On the other hand, it has been observed that the impact resistance of the same specimens of JC has been improved by 51-83%. These results revealed that it is possible to improve the mechanical properties of the composites with hybridization. In conclusion, our study shows that bio-composites can be designed according to the requirement of the application. Hence, the application areas of bio-composites can be widened with increased usage rates.
Keywords: Luffa fiber; jute fiber; hybrid composite; biocomposite; natural fiber; flexural strength; HYBRID COMPOSITES